Regulation of ventilation in the caiman (Caiman latirostris): effects of inspired CO2 on pulmonary and upper airway chemoreceptors - Tattersall, G. J.; de Andrade, D. V.; Brito, S. P.; Abe, Augusto Shinya [UNESP]; Milsom, W. K. (Springer, 2006)
In order to study the relative roles of receptors in the upper airways, lungs and systemic circulation in modulating the ventilatory response of caiman (Caiman latirostris) to inhaled CO2, gas mixtures of varying concentrations of CO2 Were administered to animals breathing through an intact respiratory system, via a tracheal cannula by-passing the upper airways (before and after vagotomy), or via a cannula delivering gas to the upper airways alone. While increasing levels of hypercarbia led to a progressive increase in tidal volume in animals with intact respiratory systems (Series 1), breathing frequency did not change until the CO2 level reached 7%, at which time it decreased. Despite this, at the higher levels of hypercarbia, the net effect was a large and progressive increase in total ventilation. There were no associated changes in heart rate or arterial blood pressure. on return to air, there was an immediate change in breathing pattern; breathing frequency increased above air-breathing values, roughly to the same maximum level regardless of the level of CO2 the animal had been previously breathing, and tidal volume returned rapidly toward resting (baseline) values. Total ventilation slowly returned to air breathing values. Administration of CO2 via different routes indicated that inhaled CO2 acted at both upper airway and pulmonary CO2-sensitive receptors to modify breathing pattern without inhibiting breathing overall. Our data suggest that in caiman, high levels of inspired CO2 promote slow, deep breathing. This will decrease deadspace ventilation and may reduce stratification in the saccular portions of the lung.
Keywords: reptile; Caiman latirostris; caiman; control of breathing; breathing pattern; hypercarbia; hypercapnia; upper airway receptors; intrapulmonary chemoreceptors